Evolution of a bicontinuous nanostructure via a solid-state interfacial dealloying reaction. (June 2016) - Wada, Takeshi; Yubuta, Kunio; Kato, Hidemi
Abstract: The solid dealloying reaction was investigated using (Fe, Cr)-Ni and Mg diffusion couples. Ni selectively reacted with Mg and the remaining Fe and Cr formed various topologies. An etching treatment provided interconnected Fe–Cr alloy with a ligament width below 200 nm, which is about one order of magnitude finer than that obtained for dealloying with Mg melt. The formation of ordered single-crystal nanofilaments at the dealloying front suggests that the topology evolved via the recently proposed interfacial spinodal decomposition and diffusion-coupled growth mechanism. Graphical abstract: